VD_FINDINFO Décision / 2018 / 1037 vom 18. Dezember 2018 - VD Tribunal cantonal (2018)
DÉCISION D'IRRECEVABILITÉ, PRÉVENU, NON-LIEU, TORT MORAL, DOMMAGE, DOMMAGE PUREMENT ÉCONOMIQUE | 115 CPP (CH), 118 al. 1 CPP (CH), 382 al. 1 CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH), 431 al. 1 CPP